2007
DOI: 10.1177/0021998307075438
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Plain-Weave Fabric Low-Temperature Vacuum Cure Epoxy Composite: Static and Fatigue Strength at Room and High Temperatures and Practicality Evaluation

Abstract: The high cost of carbon fiber composite materials is a large barrier to their increased application. Low-temperature vacuum cure epoxy resins were developed as one way to break through this barrier. This kind of epoxy is initially cured at low-temperature in a vacuum bag and post-cured at high temperature in an air-circulating oven. This study investigated the static and fatigue mechanical properties of a low-price CFRP of this kind and evaluated its practical utility. The material tested was TRK180M carbon pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 4 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…On the other hand, the offaxis properties are matrix-dominated, and the mechanical and failure properties of the matrix are temperature dependent [38]. Similarly, with lay-ups that are more fiber-dominated, such as unidirectional and quasi-isotropic laminates, only a small dependence on temperature was detected [7,8]. PMCs, especially those that exhibit matrix-dominated properties, experience a reduction of longitudinal stiffness, ultimate strength and fatigue life at elevated temperatures (ET) [21,34,38], refer to Figure 5a and b [19].…”
Section: Temperature Dependencementioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the offaxis properties are matrix-dominated, and the mechanical and failure properties of the matrix are temperature dependent [38]. Similarly, with lay-ups that are more fiber-dominated, such as unidirectional and quasi-isotropic laminates, only a small dependence on temperature was detected [7,8]. PMCs, especially those that exhibit matrix-dominated properties, experience a reduction of longitudinal stiffness, ultimate strength and fatigue life at elevated temperatures (ET) [21,34,38], refer to Figure 5a and b [19].…”
Section: Temperature Dependencementioning
confidence: 99%
“…However, when two bundles with the same orientation are in contact, cracks can extend between them [4]. Additionally, in the case of woven [0#90] and quasi-isotropic lay-ups, such as [(45#-45)(0#90)] 2s , matrix cracks first appear in the 90° tows and then in 45° tows [7].…”
Section: Failure Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…20,21 Consequently, these changes will have detrimental effects on the endurance limit and the fatigue life of the material. Several authors 2227 have reported and validated the aforementioned hygrothermal effects on unidirectional, off-axis, and woven carbon fiber reinforced plastic (CFRP) composites from their studies at various temperature and moisture levels where coupons were subjected to static and fatigue tests. Reported hygrothermal effects included: (a) deterioration of fiber/matrix interface, due moisture absorption—especially at the fabrication stage, (b) enhanced damage accumulation rate in materials due to temperature, (c) reduced static strength (tensile and compressive) and fatigue life of the material due to temperature and humidity, (d) significant reduction of the fatigue resistance or performance during fatigue in T – C compared to fatigue in T – T , and (e) significant shrinking of anisomorphic constant fatigue life diagrams with the increase of temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature in the laboratory was controlled by an air conditioner at around 23°C throughout the year. Static and fatigue tests at high temperatures used an air-circulating environmental chamber (Shimokawa et al, 2007). Elevated temperature tests were mainly conducted at 150°C, as indicated in Since these tests were carried out to determine their temperature dependence, only a few specimens were tested for each case, as shown in Table 1.…”
mentioning
confidence: 99%